An electrochemiluminescence aptasensor for diethylstilbestrol assay based on resonance energy transfer between Ag3PO4-Cu-MOF(ii) and silver nanoparticles. Issue 13 (8th June 2021) - Su, Chang; Song, Qingyuan; Jiang, Ding; Dong, Chunping; Shan, Xueling; Chen, Zhidong
Abstract : A novel electrochemiluminescence (ECL) aptasensor based on resonance energy transfer between Ag3 PO4 -Cu-MOF(ii ) and silver nanoparticles for the determination of diethylstilbestrol. Abstract : In this work, a novel electrochemiluminescence (ECL) aptasensor based on the resonance energy transfer (RET) effect between Ag3 PO4 -Cu-MOF (ii ) and silver nanoparticles (Ag NPs) is proposed. The ECL emission spectra of Ag3 PO4 -Cu-MOF and the ultraviolet absorption spectra of Ag NPs showed a good spectral overlap. Based on this, we designed an "on–off–on" ECL sensing strategy for the sensitive and specific detection of diethylstilbestrol (DES). Under the optimal conditions, the linear range of the sensor for DES detection was 1.0 × 10 −12 –1.0 × 10 −4 M, with a detection limit of 7.2 × 10 −13 M (S/N = 3). The method showed simple and fast operation, high sensitivity and selectivity, a strong anti-interference ability and good stability. More importantly, the developed aptasensor exhibited excellent recognition towards residual DES in actual water samples. The sensor has superior measurement capability and potential application value in the field of environment water quality monitoring.